Parental socioeconomic status, school physical facilities availability, and students’ academic performance - Werang, Basilius Redan; Agung, Anak Agung Gede; Sri, Anak Agung Putri; Leba, Seli Marlina Radja; Jim, Edmond Leonard (Edelweiss Applied Science and Technology, 2024)
Education is a key driver in reducing poverty and increasing shared prosperity. This study aimed to examine the impact of parental socioeconomic status and the school’s physical facilities availability on academic performance. A quantitative survey research approach was utilized taking the state junior high school students in Southern Papua Province, Indonesia, as the population and samples. Data on parental socioeconomic status and the school’s physical facilities availability were gathered using two quantitative survey questionnaires, while data on student academic performance was obtained by getting the surveyed students’ academic records. The obtained data were subjected to statistical analysis using the SPSS software version 21. The results revealed a significant positive impact of parental socioeconomic status and the school’s physical facilities availability on academic performance among the state junior high school students in Southern Papua Province, Indonesia, both partially and simultaneously. The result highlights the importance of addressing the disparities in access to quality education between students from different socioeconomic backgrounds. This study’s findings may endorse the efforts to eliminate class-based gaps in students’ academic performance in compulsory education. In addition, government policy on the socioeconomic status of parents and school grants should be implemented thoroughly to promote educational equity so that students from low economic backgrounds have equal access to quality education.